An Architecture for Agent’s Risk Perception - Luis ANTUNES; Nuno TRINDADE (Advances in Distributed Computing and Artificial Intelligence Journal, 2013)
One of the critical issues in agent’s risk decisions is perception, specially because it assumes a key role on the decision process. This subject has not received enough attention in agent’s modelling literature. Until now, the main focus has been on the decision making process of agent’s and consecutive interpretation of their behaviours. In this sense, risk literature needs to focus on perception. It is through this cognitive process that all relation between individuals and the risk event will be recognized. In this sense, agent’s make decisions about a specific type of risk by taking into account their own perception. To help understanding how perception works, it became necessary to design the mechanisms and consequent context dimensions involved on it. Following this objective, we defined an architecture explaining this cognitive process. An architecture for agents’ risk perception complemented by the associated factors of context dimensions, in order to understand this subjective process, that happen in our minds  .